A STUDY TO EVALUATE THE EFFECTS OF A NEUROMUSCULAR INJURY PREVENTION PROGRAMME (GAA 15) IN ADOLESCENT MALES PARTICIPATING IN HURLING. Issue 4 (1st February 2017) - Kelly, Sean; Lodge, Clare; Miley, Paul
Abstract : Background: Adolescents involvement in organised sport has never been more popular with post primary school students in Ireland, however, this increased level of activity has reportedly caused concern regarding the potential risk and severity of sporting injuries. Objective: The aim of the current investigation was to assess and critically analyse the application and implementation of a neuromuscular injury prevention programme (GAA 15) in adolescent males participating in hurling at post primary school level. Design: Randomised control trial. Setting: Second level post primary schools youth sport. Patients (or Participants): 518 male subjects aged 13–18.5 years were recruited from fourteen post primary schools, seven schools participated in the intervention group and seven in the control group. Interventions (or Assessment of Risk Factors): The intervention group implemented an injury prevention warm-up programme, namely the GAA 15, before every training session and matches. The control group adopted their normal warm-up behaviour prior to matches and training. Main Outcome Measurements: Epidemiological injury rate ratio (IRR) and injury proportion (IP) was compared between the two groups. Results: Hurling training injury rates of 16.51/1000 hrs. (95% CI: 9.9–23.1) and 9.16/1000 hrs. (95% CI: 5.5–12.8) were recorded for the control and intervention groups respectively. Match injury rates of 36.32/1000 hrs. (95% CI: 21.1–51.5) and 25.62/1000 hrs. (95% CI: 16.9–34.4) were reported for the control and intervention groups. Lower extremity injuries made up 75% of all injuries recorded with the hamstring being the most frequently injured body part. Hurling training lower extremity injuries were reduced by 45% and match injuries by 29% in the intervention group when compared to the control group. Conclusions: Following this investigation, it can be concluded that positive outcomes can be achieved from the implementation of a neuromuscular injury prevention warm-up, namely the GAA 15, to reduce lower extremity injuries in adolescent males participating in hurling.